TINJAUAN FASILITAS SANITASI KAPAL MOTOR RATU MARIA JURUSAN MANADO-TALAUD TAHUN 2010 - Hengky Y. Mandagie (Jurnal Kesehatan Lingkungan, 2011)
Sanitation ship is all the effort devoted to environmental factors within the vessel to break the disease transmission chain in order to enhance the degree of health. This type of research that is included in the descriptive study with the aim to describe the condition of Motor Vessel Sanitation Facilities of KM Maria Express. Methods of data collection using forms with direct observation and examination of the results of laboratory tests. Laboratory findings show that processed foods in jasaboga no E. coli bacteria, but food prepared in KM. Queen Mary E. Coli are bacteria, and samples of tap water main and storage tank on the ship contained Coliform bacteria. Port Health Office Manado need to improve routine surveillance of the vessel sanitation.